Partial Nitritation/Anammox and biological phosphorus removal integration in a single bioreactor under mainstream conditions. (April 2023) - Jia, Zhen; Yuan, Quan; Roots, Paul; Sabba, Fabrizio; Rosenthal, Alex F.; Kozak, Joseph A.; Wells, George F.
Graphical abstract: Highlights: Novel intensified bioprocess for simultaneous single-stage robust nutrient removal. Mainstream partial nitritation/anammox integration with biological phosphorus removal. Parallel strategies allowed efficient nitrite-oxidizing bacteria activity suppression. Enrichment of anammox bacteria and Tetrasphaera polyphosphate accumulating organisms. Abstract: Anammox-based nitrogen removal and enhanced biological phosphorus removal (EBPR) are increasingly applied for nutrient removal from wastewater, but are typically operated in separate reactors. Here, a novel process for integrated partial nitritation/anammox (PN/A) and EBPR in a single reactor employing integrated fixed film activated sludge was tested. The reactor was fed with mainstream municipal wastewater (5.4 ± 1.3 g COD/g N) at 20 °C for 243 days. Robust ammonium, total inorganic nitrogen, and orthophosphate removal efficiencies of 94 ± 4 %, 87 ± 7 % and 92 ± 7 % were achieved. Nitrite-oxidizing organisms suppression and ammonia-oxidizing organisms retention were achieved via solids retention time control, intermittent aeration, and suspended versus attached biomass population segregation. The contribution of anammox to nitrogen removal increased from 24 % to 74 %. In parallel, a substantial enrichment of Tetrasphaera polyphosphate accumulating organisms was observed. This work demonstrates a novel intensified bioprocess coupling PN/A and EBPR in the same reactor for efficient nutrient removal from wastewater.